2007
DOI: 10.1002/app.26671
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on quiescent crystallization kinetics of isotactic polyolefins

Abstract: Quiescent melt crystallization rates of various polyolefins including high density polyethylene (PE), isotactic form of polypropylene (PP), polybutene-1 (PB1), and poly(4-methyl pentene-1) (P4MP1) were investigated under both isothermal and nonisothermal conditions using differential scanning calorimetry (DSC). The order of overall crystallization rates under quiescent conditions from fast to slow was found to be: PE, P4MP1, PP and PB1. The Avrami equation was used to analyze isothermal and nonisothermal cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…These results mean that crystallization proceeds during quenching, even at the previous cooling rate of 10 000 K s −1 . It is also clear that the crystallization rate of PMP is faster than that of PP, and this trend coincides with the literature examined by conventional DSC . For PP/PMP blends (Figure C), the thermal signals of PP (below 160°C) and PMP (above 160°C) are separated into different temperature regions.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…These results mean that crystallization proceeds during quenching, even at the previous cooling rate of 10 000 K s −1 . It is also clear that the crystallization rate of PMP is faster than that of PP, and this trend coincides with the literature examined by conventional DSC . For PP/PMP blends (Figure C), the thermal signals of PP (below 160°C) and PMP (above 160°C) are separated into different temperature regions.…”
Section: Resultssupporting
confidence: 87%
“…It is also clear that the crystallization rate of PMP is faster than that of PP, and this trend coincides with the literature examined by conventional DSC. [12] For PP/PMP blends ( Figure 6C), the thermal signals of PP (below 160 C) and PMP (above 160 C) are separated into different temperature regions. Below 160 C, the shape of FSC curves of PP/PMP blends agreed with that of the PP homopolymer.…”
Section: Crystallinity Of Quenched Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of ÁH f * for PMP and PP are 117.2 and 209.00 J/g, respectively. 21,22 The calculated data are listed in Table 1. It showed that the crystallinity of PMP (X c, PMP ) did not show significant variation with the increase in the amount of PP in the blends until the amount of PP of the blend reached 80 wt%.…”
Section: Nonisothermal Crystallization Behavior Of Pmp/pp Blendsmentioning
confidence: 99%